Communist threat to the United States through the Caribbean. Hearings before the Subcommittee to Investigate the Administration of the Internal Security Act and Other Internal Security Laws, of the Committee on the Judiciary, United States Senate. Eighty-sixth congress, first session. Tom. I: Testimony of Maj. Pedro L. Diaz Lanz, July 14, 1959 (United States Government Printing Office, 1959)
With index.